TIGA FASE SEJARAH BERDASARKAN PEMIKIRAN IBNU KHALDUN DALAM SEJARAH INDONESIA - Bethari Widiya Hardanti (Historiography: Journal of Indonesian History and Education, 2021)
Ibn Khaldun is a philosopher with the title of the father of sociology as well as the foundation stone of history. During his life, Ibn Khaldun has produced many works. One of his world-famous works his Muqaddimah. In the Muqaddimah book, Ibn Khaldun talks a lot about historical philosophy. In addition, in the book, Muqaddimah Ibn Khaldun also describes the three phases of history, of which the three phases include the primitive phase, the village civilization phase, and the splendor phase. In Indonesia, the three phases correspond to the historical period. In Indonesian history, the primitive phase corresponds to the conditions of society during the Pleistocene and Post-Pleistocene periods, while the phase of village civilization is under the conditions of the community during the cultivation and negotiation period, as well as the splendor phase under the conditions of the community during the Hindu-Buddhist kingdom and the Islamic Sultanate. In every phase, Indonesian society has undergone many changes and developments. Both in the economic and socio-cultural fields.Ibnu Khaldun merupakan seorang filsuf dengan gelar sebagai bapak sosiologis sekaligus sebagai peletak dasar ilmu sejarah. Selama hidupnya Ibnu Khaldun telah banyak menelurkan hasil karya. Salah satu karyanya yang terkenal di dunia yaitu Muqaddimah. Didalam kitab Muqaddimah Ibnu Khaldun banyak membicarakan mengenai filsafat sejarah. Selain itu didalam kitab Muqaddimah Ibnu Khaldun juga memaparkan mengenai tiga fase sejarah, yang mana tiga fase tersebut meliputi fase primitif, fase peradaban desa dan fase kemegahan. Di Indonesia tiga fase terssebut sesuai dengan periode sejarahnya. Dalam sejarah Indonesia fase primitif sesuai dengan kondisi masyarakat pada masa Plestosen dan Pasca Plestosen, sedangkan fase peradaban desa sesuai dengan kondisi masyarakat pada masa bercocok tanam dan masa perundagian, serta fase kemegahan sesuai dengan kondisi masyarakat masa kerajaan Hindu-Budha dan Kesultanan Islam. Dalam setiap fase masyarakat Indonesia banyak sekali mengalami perubahan dan perkembangan. Baik dalam bidang ekonomi maupun sosial budaya.